Developing a zebrafish model of epidermolysis bullosa - Kahsay, Abraha Gebregziabher (2019)
Skin forms the physical boundary between internal and external environment being the first line of defense against insults. It is composed of variety of cells expressing specific molecules that maintain the normal structural integrity and function. One family of molecules includes keratins which are cytoskeletal complex proteins that form intermediate filaments in the epithelial cells. However, the entire organization and function of keratin networks can be disrupted because of single mutation in one of these molecules, leading to the inherited skin disease, epidermolysis bullosa simplex, an inherited skin disorder characterized by the formation of blisters. Zebrafish has not been extensively used to model human skin diseases to date. Hence, the main target of this work is establishing robust models of heritable skin diseases in zebrafish, focusing mostly on basal keratinocytes bullosa diseases to understand their molecular pathomechanism in vivo. Here we have generated transgenic lines overexpressing mutant forms of zebrafish Krtt1c19e and human KRT14 proteins, which are associated with generation of epidermolysis bullosa simplex in humans. Confocal analysis of immunostained zebrafish larvae expressing these mutant forms of KRT14 and Krtt1c19e showed subtle differences in keratin distribution in basal cells, but which produce keratin aggregates and dramatic alterations in keratin architecture upon heat and cold stress, suggesting that mutant keratins are affecting proper keratin dimerization process. We also found that there is cell adhesion disruption and keratinocytes detachment in the epidermolysis bullosa simplex zebrafish model via live imaging of basal XIII keratinocytes. In addition, using the CRISPR/Cas9 system, we generated col7a1 null zebrafish to establish a dystrophic epidermolysis bullosa zebrafish model. As of yet, no blistering has been observed under normal condition and proteomics analysis was carried out to check the status of the protein in the col7a1 double knockout fish. We found upregulation of three collagens; Col28a2a, Col6a2 and Col14a1b. Overall, this study provides new insights into understanding cellular and molecular defects in vivo and establishes a platform for testing human epidermolysis bullosa simplex patient genetic lesions and development of therapeutic screens.